Cystatin C is a potential predictor of unfavorable outcomes for cerebral ischemia with intravenous tissue plasminogen activator treatment: A multicenter prospective nested case–control study. (26th December 2020) - Chang, Zihan; Zou, Haiqiang; Xie, Zhenchao; Deng, Bin; Que, Rongfang; Huang, Zifeng; Weng, Guomei; Wu, Zhihuan; Pan, Ying; Wang, Yanping; Li, Mengyan; Xie, Huifang; et al.
Abstract: Background and purpose: The aim of this study was to explore whether cystatin C (CysC) could be used as a potential predictor of clinical outcomes in acute ischemic stroke (AIS) patients treated with intravenous tissue plasminogen activator (IV‐tPA). Methods: We performed an observational study including a retrospective analysis of data from 125 AIS patients with intravenous thrombolysis. General linear models were applied to compare CysC levels between groups with different outcomes; logistic regression analysis and receiver‐operating characteristic curves were adopted to identify the association between CysC and the therapeutic effects. Results: Compared with the "good and sustained benefit" (GSB) outcome group (defined as ≥4‐point reduction in National Institutes of Health Stroke Scale or a score of 0–1 at 24 h and 7 days) and the "good functional outcome" (GFO) group (modified Rankin Scale score 0–2 at 90 days), serum CysC baseline levels were increased in the non‐GSB and non‐GFO groups. Logistic regression analysis found that CysC was an independent negative prognostic factor for GSB (odds ratio [OR] 0.010; p = 0.005) and GFO (OR 0.011; p = 0.021) after adjustment for potential influencing factors. Receiver‐operating characteristic curves showed the CysC‐involved combined models provided credible efficacy for predicting post‐90‐day favorable clinical outcome (area under the curve 0.86; p < 0.001). Conclusions: Elevated serum CysC is independently associated with unfavorable clinical outcomes after IV‐tPA therapy in AIS. Our findings provide new insights into discovering potential mediators for neuropathological process or treatment in stroke. Abstract : Elevated serum cystatin C (CysC) is independently associated with unfavorable clinical outcomes in acute ischemic stroke (AIS) patients after intravenous recombinant tissue plasminogen activator (IV‐tPA) treatment. Compared with CysC alone, the CysC‐involved predictive models show higher efficacy for distinguishing IV‐tPA‐treated AIS patients with good outcomes from those with poor outcomes.